Catechin or quercetin guests in an intrinsically microporous polyamine (PIM-EA-TB) host: accumulation, reactivity, and release - Mariolino Carta (RSC Advances, 2021)
Microporous polymer materials based on molecularly "stiff"structures provide intrinsic microporosity, typical micropore sizes of 0.5 nm to 1.5 nm, and the ability to bind guest species. The polyamine PIM-EA-TB contains abundant tertiary amine sites to interact via hydrogen bonding to guest species in micropores. Here, quercetin and catechin are demonstrated to bind and accumulate into PIM-EA-TB. Voltammetric data suggest apparent Langmuirian binding constants for catechin of 550 (±50) × 103 M-1 in acidic solution at pH 2 (PIM-EA-TB is protonated) and 130 (±13) × 103 M-1 in neutral solution at pH 6 (PIM-EA-TB is not protonated). The binding capacity is typically 1 : 1 (guest : host polymer repeat unit), but higher loadings are readily achieved by host/guest co-deposition from tetrahydrofuran solution. In the rigid polymer environment, bound ortho-quinol guest species exhibit 2-electron 2-proton redox transformation to the corresponding quinones, but only in a thin mono-layer film close to the electrode surface. Release of guest molecules occurs depending on the level of loading and on the type of guest either spontaneously or with electrochemical stimuli.